Stereoselective synthesis of fused tetrahydroquinazolines through one-pot double [3 + 2] dipolar cycloadditions followed by [5 + 1] annulation - Zhang, Xiaofeng; Pham, Kenny; Liu, Shuai; Legris, Marc; Muthengi, Alex; Jasinski, Jerry P.; Zhang, Wei (Beilstein Journal of Organic Chemistry, 2016)
The one-pot [3 + 2] cycloaddition of an azomethine ylide with a maleimide followed by another [3 + 2] cycloaddition of an azide with the second maleimide gives a 1,5-diamino intermediate which is used for a sequential aminomethylation reaction with formaldehyde through [5 + 1] annulation to afford a novel polycyclic scaffold bearing tetrahydroquinazoline, pyrrolidine, pyrrolidinedione, and N-substituted maleimide in stereoselective fashion.
Keywords: [5 + 1] annulation; [3 + 2] cycloaddition; one-pot reactions; stereoselective synthesis; tetrahydroquinazoline